RFID technology application in the aviation industry. - José Alberto Raimundo Paulo (2007)
Radio Frequency Identification (RFID) technology applications have being deeply discussed and studied lately by different types of industries due to its huge potential benefits to the business operations as a whole. This work will briefly address one of the main issues involved on these discussions: the first steps to perform a Return on Investment Analysis (ROI) and also some important technical concerns in order to achieve the best cost and benefits scenario possible focused on the aviation industry logistics environment.